Robust and artifact-free mounting of tissue samples for atomic force microscopy. (January 2014) - Morgan, Joshua T.; Raghunathan, Vijay Krishna; Thomasy, Sara M.; Murphy, Christopher J.; Russell, Paul
Immobilization of tissue-samples for atomic for microscopy (AFM) is typically done using either semi-dry tissue or by gluing the tissue sample down, both of which can introduce artifacts. Here, we describe the design of a Soft- Clamping Immobilizing Retainer of Tissue (SCIRT) for consistent and nondestructive immobilization of tissues for AFM analysis. We compare the performance of our SCIRT method with glue-immobilization for two difficult to handle tissue types: human trabecular meshwork (HTM) and rabbit cornea (RC). Our results demonstrate that the SCIRT method has several advantages, including: ( i ) allowing for small sample sizes, ( ii ) enabling continuous hydration, ( iii ) eliminating contact with glue or associated solvents, ( iv ) permitting sample recovery following measurement, and ( v ) ease of use. In conclusion, the SCIRT method is a simple and effective means of immobilizing soft, hydrated tissue samples consistently and without artifacts.